DESAIN DAN PENGEMBANGAN LKPD BERORIENTASI KOMPLEKSITAS KONTEN DAN PROSES KOGNITIF PADA MATERI FLUIDA STATIS UNTUK PEMBELAJARAN FISIKA KELAS XI SMA/MA - Firda Rahmatika; Amali Putra; Yurnetti Yurnetti (PILLAR OF PHYSICS EDUCATION, 2017)
Physics learning is aimed to develop the competence of students that includes aspects of the attitude, knowledge, and skill. The learning objectives are grouped by six levels of cognitive processes that are tailored to the revision of Bloom's taxonomy. The sixth level are combined with the four dimensions of knowledge contained in the physics lesson content. In fact, the attainment of students is not as expected. One of the  solution offered is the use of quality teaching materials, for example worksheet. In general, the school has not been found worksheet which includes four dimensions of knowledge, and six levels of cognitive processes. In this study developed worksheet oriented complexity of content and cognitive processes in a static fluid material. Worksheet design in terms of validity, the practicality and effectiveness. The method used is a research and development (R & D). The model of this research is 4D reduced to 3D comprising the step of define, design, and development. This research subjectis 30 students of class XI SMAN 10 Padang. The object of this research is the design of LKPD oriented complexity of contents and cognitive processes in the static fluid material for learning physics class XI SMA/MA.Collecting data in this study using a validation sheet given to the validator. Data practicalities of using instruments distributed to the practicalities of Physics teachers and students in class XI MIA. Efficacy data derived from the value of N-gain. The research showed the validity of the validator is at 82.51 with very valid criteria. Practicalities of test results by the teacher obtained a value of 94.58 with a very practical criterion and by students at 90.61 with very practical criteria. The effectiveness of the test results obtained by the value of N-gain of 0.67 with the criteria of being. Thus this research has resulted LKPD complexity oriented content and cognitive processes are valid, practical, and effective.